PENYELENGGARAAN PEMERINTAH DALAM MEWUJUDKAN BIROKRASI MENUJU PRAKTEK GOOD GOVERNANCE DI KECAMATAN PAUH KOTA PADANG - Juliandari, Agnes; Puryanto, Puryanto; Ratny Pasaribu, Fani; Ariyati, Yumi; Krisno, Onzu; Khudri, Nursaadah (Ensiklopedia of Journal, 2025)
The purpose of this research is to find out the government's implementation in realizing Good Governance bureaucracy in Pauh District, Padang City, to find out the obstacles and also to find out what efforts must be made to overcome obstacles in government administration in realizing Bureaucracy towards Good Governance practices in Pauh District, Padang City.  The research method used in this research is a descriptive research method with a qualitative approach. The data sources in this research consist of primary sources directly from informants and 7 sources and also observations.  Secondary sources come from documents and field documents. The results of this research are 9 concepts used in the formation of Good Governance in Pauh District, Padang City, namely community participation, upholding the supremacy of law, transparency, care for stakeholders, community orientation, equality for all communities, effectiveness and efficiency, accountability and strategic vision. .  The obstacles that occur are lack of community participation, abuse of power, lack of transparency, differentiating communities according to socio-economics, not being community oriented, services that are less effective and efficient, and lack of accountability in services. Efforts made to overcome the problem are by quickly correcting misunderstandings between employees and the community, recruiting employees and conducting training, not discriminating between services to the community, leaders are required to equalize the community from an economic and social perspective, work programs must be completed in accordance with subject, object, predicate. Keywords: Administration, Good Governance, Bureaucracy